LEARNED-CENTERED EDUCATION USING THE FLIPPED CLASSROOM METHOD- GOOD PRACTICE AND EXPERIENCES - TOTH-BAKOS, Anita; MESZAROS, Timea; MESZAROS, Attila; CSEHIOVA, Agata (Trends in education, 2024)
The main theme of the study is the use of the flipped classroom method as a possible alternative to learner-centred teaching. The main goal of the flipped classroom method is to make class time as active as possible for the students. In doing so, they learn through their own experiences and active work. This makes the learning environment more learner-centred, which has a positive impact on learners' attitudes, motivation and quality of educational process. The paper summarizes good practice in the application of the method, and the experience and results are gathered. The pilot application has been implemented at the Faculty of Education of J. Selye University in the academic year 2022/23 within the Erasmus+ project ``Developing Flipped Methods for Teaching''. The aim of the study is to present in detail the steps and elements of the application of the flipped classroom with the focus being on classroom activities. The results of the pre-tests and post-tests, as well as student and teacher feedback, will be presented to assess the application of the method. The main aim of the work is to demonstrate the application of the method in practice as an inspiration to increase its widespread awareness and use.
Keywords: learner-centred education; flipped classroom method; psychology; pre-class activities; in-class activities; post-class activities